Toplotni otok Ljutomera - Ivajnšič, Danijel (Geografski obzornik, 2010)
Not just in big cities, even in small towns the so called urban climate is evident. People produce a lot of surplus energy in towns. Asphalt and concrete surfaces are constantly changing not only the energy balance but also the water balance of the city. High buildings in cities have an influence on the local air circulation creating specific wind conditions. In this research we represent a specific climate of Ljutomer - the temperature differences between the town and its surroundings, the morphology and intensity of the urban heat island according to the different weather types as well as the daily temperature changes of the Ljutomer urban heat island.
Keywords: Ljutomer; mesta; microclimate; mikroklima; Slovenia; Slovenija; temperatura; zrak